1968
DOI: 10.1021/ac60268a017
|View full text |Cite
|
Sign up to set email alerts
|

Reaction rate measurements with fluoride ion-selective membrane electrode. Formation kinetics of ferrous fluoride and aluminum fluoride complexes

Abstract: slowly changing signals. In Table II results are presented for rapidly changing synthetic signals. Resistor R¡ was changed to 15K and integrator times of 50 msec were used for measuring these slopes. Relative errors are again within 0.1% and relative standard deviations are about 0.2%.Results for the determinations of phosphate by the reaction rate procedure are shown in Table III. These results were based on a single phosphate standard. In Table IV results of automatic determinations of glucose in the 5-20 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 6 publications
1
13
0
2
Order By: Relevance
“…If we assume HF and F -to be the predominant fluoride-containing species in FIA experiments their concentrations, with variation in pH, can be calculated from the formation constant of HF. Previous investigation [8] has shown that both species can take part in iron-fluoride complex formation. Also, for the same total fluoride and iron concentrations, the rate of formation of iron-fluoride complex depends on the acidity of the solution.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…If we assume HF and F -to be the predominant fluoride-containing species in FIA experiments their concentrations, with variation in pH, can be calculated from the formation constant of HF. Previous investigation [8] has shown that both species can take part in iron-fluoride complex formation. Also, for the same total fluoride and iron concentrations, the rate of formation of iron-fluoride complex depends on the acidity of the solution.…”
Section: Resultsmentioning
confidence: 91%
“…Suitability of the FISE for monitoring a reasonably fast reaction of the formation of FeF 2+ in acidic solution has been previously established [8]. Oehme and Dolezalova [9] reported the possibility of direct potentiometric determination of Fe 3+ based on iron-fluoride complex formation but no detailed information was given.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto sugiere que el almacenamiento en medio ácido, favorece la liberación del flúor formando compuestos de calcio y lantano. Existe alguna evidencia de que el aluminio se puede asociar con fluoruro, con el cual, es sabido, que se compleja fuertemente [33]. WILSON [7] postuló la presencia de especies complejas del tipo AlF 2+ y AlF 2 + entre los iones lixiviados de los ionómeros de vidrio.…”
Section: Variación De La Composición Elemental De La Superficie Del Iunclassified
“…Combination of the simplicity of the kinetic method with the advantages of this sensor (low detection limit, high selectivity) produces an excellent analytical technique for determination of metal ions that form complexes with fluoride. Suitability of the FISE for monitoring a reasonable fast reaction of the formation of FeF 2+ in acidic solution has been established by Srinivasan and Rechnitz [5]. Determination of Fe(III), based on monitoring of the formation of FeF 2+ using FISE is described [6].…”
Section: Use Of Potentiometric Chemical Sensors In Aqueous Solutionmentioning
confidence: 99%